Pengenalan Aspek Perpajakan Pada Pelatihan Pengelolaan Keuangan BUMDes di Kecamatan Bontoa Kabupaten Maros: Pengenalan Aspek Perpajakan Pada Pelatihan Pengelolaan Keuangan BUMDes - Syiar Rinaldy; Ruslan Ruslan; Gunawan Gunawan; Ardiansyah Halim (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
Taxes are one of the sources of government funds to carry out development, both central and local governments. The potential for taxes originating from BUMDes efforts is quite large, so activities to increase knowledge through socialization, training or the like about taxation aspects must be intensively carried out. The purpose of this community service activity is to increase the knowledge of BUMDes managers in understanding and carrying out tax obligations and not making tax calculations and reporting errors. The target of the activity is the BUMDes manager in Bontoa District. The method of the activity goes through three stages, namely the first stage of site survey, the second stage of planning needs and training materials and the third stage of implementation of activities and evacuation. Implementation of activities in the form of training with lecture methods, discussions and simulation activities. The evaluation method is in the form of direct observation during the activity and analysis of the results of the questionnaire (questionnaire). The results of the activity show that there is an increase in management knowledge in taxation imposed on BUMDes businesses. Follow-up activities in the form of training and technical guidance related to the taxation aspects of BUMDes.